X-ray metrology of an array of active edge pixel sensors for use at synchrotron light sources - Plackett, R; Arndt, K; Bortoletto, D; Horswell, I; Lockwood, G; Shipsey, I; Tartoni, N; Williams, S (Elsevier, 2017)
We report on the production and testing of an array of active edge silicon sensors as a prototype of a large array. Four Medipix3RX.1 chips were bump bonded to four single chip sized Advacam active edge n-on-n sensors. These detectors were then mounted into a 2 by 2 array and tested on B16 at Diamond Light Source with an x-ray beam spot of 2um. The results from these tests, compared with optical metrology demonstrate that this type of sensor is sensitive to the physical edge of the silicon, with only a modest loss of efficiency in the final two rows of pixels. We present the efficiency maps recorded with the microfocus beam and a sample powder diffraction measurement. These results give confidence that this sensor technology can be used effectively in larger arrays of detectors at synchrotron light sources.